Preparation of Oligosaccharides by Degradation of Polysaccharides from Chinese Jujube and Its Biological Activity. (19th April 2018) - Yan, Xu; Wang, Weiwei; Liu, Mengjun; Zhao, Zhihui
Abstract : This study examined the degradation of polysaccharides to oligosaccharides in Chinese jujube fruits. Using a response surface model, the degradation conditions of polysaccharides under acid hydrolysis and enzymatic hydrolysis were optimized in laboratory conditions. A degradation rate of 66.9% was obtained under optimum acid hydrolysis conditions: 0.6 mol/L hydrochloric acid, 3% substrate concentration, and 1 h reaction time. A degradation rate of 41.4% was obtained under optimum enzyme hydrolysis conditions: 4.0 mL cellulose solution (10 mg/mL), 0.3 mL substrate solution (20 mg/mL), 0.7 mL citric acid buffer solution (pH 5), and 7.3 h reaction time. Using the stimulation effect for strain J-4 intestinal probiotic proliferation, the biological activity of oligosaccharides was determined. The results showed that the oligosaccharides from enzyme hydrolysis encouraged intestinal probiotic proliferation.